AI, education, and children’s rights - Holmes, Wayne (Frontiers in Education, 2025)
Artificial Intelligence (AI) systems are increasingly being used in education. However, the impact that these AI systems are having on children’s rights is mostly overlooked. This paper aims to further a discussion around that omission. Having first explored how AI is distinct from other digital technologies (because its mimicry of human behaviours leads to misconceptions about its capabilities), the paper introduces the United Nations Convention on the Rights of the Child (UNCRC), which establishes key rights for children: the rights to education, dignity, autonomy, privacy, and protection from discrimination and from economic exploitation. Each of these rights are then considered in turn, focusing on how AI systems are complicating things. For example, AI systems lack the empathy and intuition of human teachers, risking the undermining of children’s dignity; while the exploitation of children’s data by commercial AI developers means that children are working as unpaid labour. The paper concludes by arguing that more ethical research is needed to understand AI’s impact on children’s cognitive development and rights; while policymakers, educators, and developers must prioritise children’s rights and well-being over the contested benefits of AI, to ensure full alignment with children’s rights principles.